رؤية أعضاء هيئة التدريس لكفايات معلم تعليم الكبار في ضوء التحول الرقمي للمجتمع المصري - النجار، فاطمة رمضان عوض (جامعة سوهاج - كلية التربية, 2021)
هدفت الدراسة الحالية إلى تحديد كفايات معلم تعليم الكبار في ضوء التحول الرقمي للمجتمع المصري من وجهة نظر أعضاء هيئة التدريس بجامعات مصر، وتم تطبيق استبانة إلكترونياً على عينه من أعضاء هيئة التدريس بلغ عددها (30) عضو من جامعة (القاهرة، حلوان، عين شمس، المنصورة، بنها، بنى سويف، كفر الشيخ، دمنهور، طنطا) وتتضمن الاستبانة (7) محاور هي الكفايات (الشخصية)، (المهنية)، (الأكاديمية)، (الثقافية والاجتماعية)، (التكنولوجية والرقمية)، (الأخلاقية)، (إدارة الصف) بواقع (65) عبارة هي معارف ومهارات واتجاهات يجب أن يمتلكها معلم تعليم الكبار في ضوء التحول الرقمي للمجتمع المصري، وأوصت الدراسة بضرورة: • التطوير المستمر لكفايات معلم الكبار بما يتناسب مع متطلبات التحول الرقمي. • التخطيط لبرامج تكوين معلم الكبار مع وضع أهداف واضحة ومحددة تتناسب مع متطلبات التحول الرقمي ويمكن قياسها. • وضع سياسة موحدة ومناسبة لتحديات القرن الحالي لعملية تكوين معلم الكبار على مستوى كليات التربية، وكذلك انتقاء واختيار معلمي الكبار الراغبين في العمل بهذا المجال. • تطوير برامج إعداد معلم الكبار، بحيث تنمى كفايات التدريس، والتدريب على التكنولوجيا الحديثة، واستخداماتها في التعليم. • حرص المجتمع على توفير فرص عمل للمتحررين من الأمية لضمان حياة كريمة. • توظيف التقنيات الحديثة والرقمية للتعليم في مجال محو الأمية وتعليم الكبار. • زيادة الوعي ببرامج محو الأمية من خلال الحملات الإعلامية والاتصال الجماهيري. • تفعيل دور المجتمع المدني في المشاركة مادياً وثقافياً في برامج محو الأمية وتعليم الكبار.
The current study aimed to determine the competencies of adult education teachers in light of the digital transformation of the Egyptian society from the point of view of faculty members in Egyptian universities, and an electronic questionnaire was applied to a sample of faculty members, which reached 30 members from the University (Cairo, Helwan, Ain Shams, Mansoura, Benha, Beni Suef, Kafr El Sheikh, Damanhour, Tanta) and the questionnaire includes (7) axes: (personal) competencies, (professional), (academic), (cultural and social), (technological and digital), (ethical), (management The class (65) phrases are knowledge, skills, and attitudes that an adult education teacher should possess in light of the digital transformation of Egyptian society. The study recommended that: • Continuous development of adult teacher competencies in line with the requirements of digital transformation. • Planning for adult teacher training programs with setting clear and specific goals commensurate with the requirements of digital transformation and can be measured. • Establishing a unified policy appropriate to the challenges of the current century for the process of training adult teachers at the level of colleges of education, as well as selecting and selecting adult teachers willing to work in this field. • Developing adult teacher preparation programs to develop teaching competencies, training on modern technology, and its uses in education. • Society's keenness to provide job opportunities for those who are freed from illiteracy to ensure a decent life. • Employing modern and digital technologies for education in the field of literacy and adult education. • Increasing awareness of literacy programs through media campaigns and mass communication. • Activating the role of civil society in participating financially and culturally in literacy and adult education programs.
الجزء الثاني. يوليو 2021
Keywords: أعضاء هيئة التدريس -- الكفايات التدريسية -- تكنولوجيا التعليم -- تدريب المعلمون -- تعليم الكبار -- مصر